Ultrastrong Coupling of Plasmons and Excitons in a Nanoshell - Cacciola, Adriano; Di Stefano, Omar; Stassi, Roberto; Saija, Rosalba; Savasta, Salvatore (ACS nano, 2014)
The strong coupling regime of hybrid plasmonic–molecular systems is a subject of great interest for its potential to control and engineer light–matter interactions at the nanoscale. Recently, the so-called ultrastrong coupling regime, which is achieved when the light–matter coupling rate reaches a considerable fraction of the emitter transition frequency, has been realized in semiconductor and superconducting systems and in organic molecules embedded in planar microcavities or coupled to surface plasmons. Here we explore the possibility to achieve this regime of light–matter interaction at nanoscale dimensions. We demonstrate by accurate scattering calculations that this regime can be reached in nanoshells constituted by a core of organic molecules surrounded by a silver or gold shell. These hybrid nanoparticles can be exploited for the design of all-optical ultrafast plasmonic nanocircuits and -devices.